2020
DOI: 10.3389/fphys.2020.588291
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chemosensory Genes in Full and Hungry Adults of Arma chinensis (Pentatomidae) Through Antennal Transcriptome

Abstract: The predatory insect Arma chinensis (Hemiptera: Pentatomidae) is widely distributed in China, where it is also used to control many agricultural and forest pests. The chemosensory genes expressed in its antennae play crucial roles in food-seeking and mating behaviors. To better understand the olfaction of A. chinensis antennae, we identified the genes related to food-seeking and mating. Sequencing of the antennal transcriptomes of full and hungry male and female A. chinensis revealed 38 odorantbinding proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
(107 reference statements)
1
8
0
Order By: Relevance
“…The expression levels of 10 differentially expressed EcorOBPs were upregulated in the feeding treatment group. Similar observations were made in other studies, such as with a study of the predator Arma chinensis, which showed that two and nine AchiOBPs were upregulated in the female and male antennae, respectively, after feeding [69]. Only EcorCSP7 was downregulated in the feeding treatment group in our study, consistent with findings in Glossina morsitans where the expression levels of GmorCSP2 increased in females after starvation for 48 h [70,71].…”
Section: Discussionsupporting
confidence: 92%
“…The expression levels of 10 differentially expressed EcorOBPs were upregulated in the feeding treatment group. Similar observations were made in other studies, such as with a study of the predator Arma chinensis, which showed that two and nine AchiOBPs were upregulated in the female and male antennae, respectively, after feeding [69]. Only EcorCSP7 was downregulated in the feeding treatment group in our study, consistent with findings in Glossina morsitans where the expression levels of GmorCSP2 increased in females after starvation for 48 h [70,71].…”
Section: Discussionsupporting
confidence: 92%
“…However, antennal transcriptomes from other predatory insects exhibited variable numbers of ORs. For instance, only 15 ORs could be identified in the antennal transcriptome of Cyrtorhinus lividipennis Reuter (Hemiptera: Miridae) [ 17 ], 14 ORs in Chrysopa pallens (Rambur) [ 14 ] and 37 ORs in Chrysoperla sinica (Neuroptera: Chrysopidae) [ 15 ], 51 ORs in Episyrphus balteatus DeGeer and 42 ORs in Eupeodes corollae Fabricius (Diptera: Syrphidae) [ 18 ], and 38 ORs in Arma chinensis (Fallou) (Hemiptera: Pentatomidae) [ 92 ]. Hopefully, further identification of OR genes in other predatory insect antennae will permit to increase coverage of probable unknown putative OR genes in these insects.…”
Section: Discussionmentioning
confidence: 99%
“…However, antennal transcriptomes from other predatory insects exhibited variable numbers of ORs. For instance, only 15 ORs could be identified in the antennal transcriptome of Cyrtorhinus lividipennis Reuter (Hemiptera: Miridae) [17], 14 ORs in Chrysopa pallens (Rambur) [14] and 37 ORs in Chrysoperla sinica (Neuroptera: Chrysopidae) [15], 51 ORs in Episyrphus balteatus DeGeer and 42 ORs in Eupeodes corollae Fabricius (Diptera: Syrphidae) [18], and 38 ORs in Arma chinensis (Fallou) (Hemiptera: Pentatomidae) [92]. Hopefully, further identification of OR genes in other predatory insect antennae will permit to increase coverage of probable unknown putative OR genes in these insects.…”
Section: Discussionmentioning
confidence: 99%